2016
DOI: 10.1159/000454654
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Dysfunction in Nonalcoholic Fatty Liver Disease and Cryptogenic Cirrhosis

Abstract: Nonalcoholic fatty liver disease (NAFLD) and cryptogenic cirrhosis (CC) are considered preneoplastic conditions that might progress to hepatocellular carcinoma. We evaluated parameters of telomere dysfunction in these patient groups to study the correlation between telomere length and the progression of NAFLD. We analyzed peripheral lymphocytes from 22 patients with NAFLD, 20 patients with CC, and 20 healthy, age-matched controls. Telomere length was analyzed using quantitative fluorescence in situ hybridizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 41 publications
(43 reference statements)
1
30
1
Order By: Relevance
“…(49) Similarly, Laish et al showed that patients with NAFLD had shorter telomeres in their peripheral lymphocytes and higher expression of telomerase reverse transcriptase mRNA as compared with healthy controls. (50) These findings support the role of telomere dysfunction and senescence in general in NAFLD.…”
Section: The Involvement Of Senescence In Human Nafld/nashsupporting
confidence: 64%
See 1 more Smart Citation
“…(49) Similarly, Laish et al showed that patients with NAFLD had shorter telomeres in their peripheral lymphocytes and higher expression of telomerase reverse transcriptase mRNA as compared with healthy controls. (50) These findings support the role of telomere dysfunction and senescence in general in NAFLD.…”
Section: The Involvement Of Senescence In Human Nafld/nashsupporting
confidence: 64%
“…Patients who developed NAFLD within this period had shorter telomeres in peripheral blood leukocytes at the end of the follow‐up period compared with the patients who did not develop steatosis . Similarly, Laish et al showed that patients with NAFLD had shorter telomeres in their peripheral lymphocytes and higher expression of telomerase reverse transcriptase mRNA as compared with healthy controls . These findings support the role of telomere dysfunction and senescence in general in NAFLD.…”
Section: The Role Of Senescence In Nafld/nashmentioning
confidence: 74%
“…Indeed, a recent study showed that hepatocyte senescence, not hepatocyte telomere shortening, is closely associated with fibrosis stage, disease progression and adverse liver‐related outcomes . Other studies have also found that shorter telomere length and increased cellular senescence was demonstrated in patients with NAFLD compared to the healthy controls along with genetic and environmental risk factors . Additionally, there is evidence that elevated inflammation, as observed in NASH with fibrosis, may be a consequence of premature immunosenescence .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to chronic lung diseases, telomere shortening has been evinced to drive the progression of liver cirrhosis in both hepatocytes and senescence associated with fibrotic scaring 8 . Apart from telomeres in the liver-specific cells, several clinical studies uncovered telomere attrition in blood leukocytes of patients with chronic liver diseases [10][11][12][13][14][15] . Collectively, it seems plausible that aberrant telomere length could be an important mediator for hepatocyte damage and turnover, and alterations in telomere length would open a unique opportunity for early detection of ATDILI progression in tuberculosis patients.…”
mentioning
confidence: 99%